Post-exercise rehydration with coconut water: as effective as a sports drink, or better? - Pérez Idárraga, Alexandra (2011)
Objective: To compare the effectiveness of fresh coconut water as a rehydration beverage with bottled water and a sports drink. Method: eleven participants, 22.0±1.9 years of age and 65.6±13.0 kg body mass (average ± S.D.), reported to the laboratory on three separate occasions, each one week apart. Each time they exercised in the heat until they were dehydrated by 1.84 ± 0.2% of initial body mass. They were then rehydrated for one hour with commercial bottled water (BW), a sports drink (SD), or coconut water (CW), using a volume equivalent to 120% of weight loss. Perceived beverage acceptance and tolerance ratings were evaluated, and urine was collected over three hours following rehydration. Results: Urine volumes showed an interaction between beverage and time (p=0.003); BW was statistically different from CW and SD, 30 and 60 minutes after rehydration (p<0.05). Total urine volume was higher for BW (625 ± 183 mL) compared with both CW and SD (390 ± 73 mL and 416 ± 200 mL, respectively, p<0.002); CW and SD were not different from each other (p>0.05). This resulted in a different fluid conservation percentage for BW (56%) compared with CW (71%) and SD (71%) (p<0.001). Perceived tolerance ratings showed no interaction between beverage and time (p>0.05). Perceived sweetness was lower for BW (p= 0.024); SD had higher scores for flavor and overall acceptance (p<0.05). Conclusions: fresh coconut water is as effective as a sports drink in terms of fluid retained following consumption, and it has good tolerance and acceptance; it could be used for rehydration provided it is accessible to the individual and the person finds the flavor pleasing.